The evolution of health services research in Austria: a bibliometric exploration of trends, themes, and collaborations - Choi, Kyung-Eun (Anna); Fitzek, Sebastian (Frontiers in Health Services, 2025)
BackgroundHealth services research (HSR) in Austria has expanded rapidly over the past two decades, reflecting the evolving need for a healthcare system that effectively addresses the broader challenges of an increasingly strained healthcare environment. Mapping the progression and focus areas of this research is essential for guiding policy-making and future studies.ObjectivesThis bibliometric study aims to chart the evolution of Austrian HSR between 2000 and 2024. By examining publication trends, thematic priorities, collaboration networks, and research impacts, the analysis provides evidence-based insights that inform healthcare strategies and highlight research gaps.MethodsA systematic literature search was conducted in PubMed, which targeted peer-reviewed articles published from 2000–July 31, 2024. In total, 81 articles met the inclusion criteria. Bibliometric methods, including coauthorship mapping, keyword co-occurrence analysis, and citation tracking, were used to identify core research themes, key authors, and institutional collaborations.ResultsAnnual publication outputs increased notably from 2019 to 2020, corresponding to the heightened focus on healthcare during the COVID-19 pandemic. The major themes included mental health, patient care, public health, and disease management, with a growing interest in telemedicine and digital solutions. The Medical University of Vienna led publication activity, and strong international ties were evident, particularly with institutions in the UK and Germany. Citation analyses revealed varied research impacts, with some highly cited studies influencing policy debates and clinical practices.ConclusionsAustrian HSR has a dynamic trajectory, reflecting evolving national priorities and global healthcare challenges. Continued efforts are needed to address gaps involving underserved populations, integrate digital health technologies, and enhance economic evaluations of primary care reforms. Furthermore, better standardization in the reporting of funding sources and conflicts of interest is recommended to strengthen methodological rigor and public trust. By fostering collaboration, transparency, and comprehensive evaluations, HSR can more effectively shape equitable healthcare policies in Austria.